A de novo CACNA1D missense mutation in a patient with congenital hyperinsulinism, primary hyperaldosteronism and hypotonia. Issue 1 (1st January 2020) - De Mingo Alemany, María Carmen; Mifsud Grau, Luis; Moreno Macián, Francisca; Ferrer Lorente, Belén; León Cariñena, Sara
ABSTRACT: Congenital hyperinsulinemic hypoglycemia is the most frequent cause of persistent and recurrent hypoglycemia in the first years of life and in many patients rare genetic variants can be identified. Recently a case of congenital hyperinsulinemic hypoglycemia and a severe neurodevelopmental syndrome due to a mutation in the voltage-gated Cav1.3 Ca 2+ channel CACNA1D gene has been reported which required long-term treatment with diazoxide. This suggested CACNA1D variants as a potential cause for this condition. Here we support this observation by presenting the case of a female child with congential hyperinsulinemic hypoglycemia and primary hyperaldosteronism, aortic insufficiency, pronounced developmental delay, muscle hypotonia, and facial dysmorphias but without seizures. Sequencing of the exome of the child and its parents identified a novel de novo CACNA1D missense mutation p.L271 H, replacing a highly conserved residue in a functionally relevant region of the voltage-gated Cav1.3 Ca 2+ channel. The patient was treated with diazoxide and nifedipine with adequate control of glucose metabolism and blood pressure, and with improvement in muscle tone. Our findings further confirm the pathogenic role of CACNA1D for congentital hyperinsulinemic hypoglycemia and primary aldosteronism. Moreover, we provide evidence that the dihydropyridine Ca 2+ channel blocker nifedipine, although not considered a first-line treatment for congenital hyperinsulinism, may be beneficial to control blood pressure and neurological symptoms in patients with CACNA1D mutations.